Comparative study of Cu2ZnSnSe4 solar cells growth on transparent conductive oxides and molybdenum substrates. (December 2019) - Temgoua, S.; Bodeux, R.; Mollica, F.; Naghavi, N.
Highlights: Se annealing leads to the CZTSe phase on the different Mo, FTO, AZO substrates. Morphology of CZTSe is affected by the TCO contacts. FTO back contact leads to the formation of the ZnO at the CZTSe/FTO interface. TCO acts as a diffusion barrier of Na from sod a lime glass to CZTSe. Efficiency up to 8% for the CZTSe solar cells deposited on Mo substrate. Abstract: Cu2 ZnSnSe4 (CZTSe) thin films have been synthetized by cosputtering followed by a selenization treatment on Mo and transparent conductive oxide (TCO) coated soda lime glass substrates, such as ZnO:Al and SnO2 :F (FTO). The aims of the present work is to investigate the impact of the TCO substrates on the CZTSe growth, the reactions at the back contact and the electrical properties of solar cells. The results show that the morphology of CZTSe is affected by the TCO back contacts. It is found that TCO acts as a diffusion barrier of Na from soda lime glass to CZTSe. Thus low incorporation of Na during the annealing could explain the difference in grain size of CZTSe deposited on TCO. Moreover it is evidenced chemical reactions between TCO and CZTSe which affects the interface. While the efficiency up to 8% is obtained for CZTSe based solar cells deposited on Mo substrate, the efficiency drops to 2.3% for the solar cells deposited on FTO. The low efficiency is explained by the recombination at the back contact due to the formation of the ZnO secondary phase at the CZTSe/FTO interface.